ULTRASOUND IMAGING OF THE SKIN IN THE DIAGNOSTIC ASSESSMENT OF PEDIATRIC ATOPIC DERMATITIS (International journal of medical sciences, 2026)
Atopic dermatitis (AD) is a prevalent chronic inflammatory skin condition in children, characterized by recurrent flare-ups and significant variability in its clinical manifestations. Timely and accurate diagnosis is crucial for optimal management and treatment, as delays or inaccuracies can lead to disease progression, complicating both treatment and prognosis. Traditional diagnostic tools such as clinical assessment, histopathology, and dermatoscopy have been widely used to assess the severity and progression of AD. However, these techniques may not provide a comprehensive picture of the underlying structural changes in the skin. Ultrasound examination of the skin has emerged as a valuable, non-invasive imaging technique that offers real-time insights into the morphological characteristics of the skin affected by atopic dermatitis. By evaluating the skin’s echogenicity, thickness, and dermal architecture, ultrasound can provide detailed information on inflammation, edema, and epidermal changes, which are key markers of disease activity. The method’s sensitivity in detecting subtle changes in both the epidermal and dermal layers allows for better differentiation between active and chronic phases of the disease. This review highlights the growing role of ultrasound examination in the diagnostic and prognostic assessment of atopic dermatitis in pediatric patients. It explores the technology's utility in early diagnosis, monitoring therapeutic responses, and predicting disease outcomes. Ultrasound’s ability to provide objective, quantitative data complements clinical evaluation and contributes to a more personalized and precise approach to patient care. The article also discusses the practical advantages of ultrasound, such as its safety, repeatability, and cost-effectiveness, making it suitable for routine use in pediatric dermatology. Thus, skin ultrasound is an emerging diagnostic tool that enhances the clinical evaluation of atopic dermatitis in children, offering a more comprehensive understanding of disease dynamics. It holds promise for improving the accuracy of diagnosis, monitoring treatment efficacy, and predicting long-term outcomes in pediatric AD patients.